An introduction to options - Shaw, Alastair; Griffiths, Nigel (London : Financial i Production, 1989)
This video consists of 5 sections : introduction, terminology, hedging srtategies, trading strategies and conclusion
This video is sponsored by Chicago Board of Trade
Writer, Nigel Griffiths, David Libbert
Keywords: Options (Finance)